Third party risk modelling in surrounding of Airport Nikola Tesla in Belgrade - Đorem Marina S.; Netjasov Feđa T. (Tehnika, 2018)
One of important safety issues in surroundings of contemporary airports is third party risk, i.e. fatality risk for individuals living, working or residing in airport vicinity caused by aircraft accident. Principles of modelling and estimation of third party risk as well as possible usage of modelling results are described in this paper. Existing models are briefly introduced with two basic third party risk indicators: individual and societal risks. An example of modelling of third party risk has been shown in case of Airport Nikola Tesla in Belgrade (only surrounding in south-east direction). Sensitivity analysis of risks values on changes of traffic volume and changes of share of departures from runway 12 and landings on runway 30 have been performed. It was found that risk increases with traffic volume as well as that risk values are more sensitive on changes in number of landings.